Digital Marketing on Organizational Agility of Saving and Credit Cooperative Organizations in Meru Town, Kenya - Nderitu, Daniel King’ori (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Savings and Credit Cooperative Organizations (SACCOs) are essential for economic growth, providing financial services such as deposits, loans, savings accounts, money transfers, insurance, and payment services. Despite the availability of digital media to enhance business processes and organizational agility, its adoption among SACCOs is relatively new. This study aimed to investigate the impact of digital marketing on the organizational agility of SACCOs in Meru Town, Kenya, focusing on social media, mobile, and website marketing. A descriptive research design was employed to examine the relationship between digital marketing and organizational agility. The study targeted five SASRA-licensed SACCOs in Meru Town, collecting data from 52 respondents through a semi-structured questionnaire and using a stratified sampling method. A pilot study with five respondents ensured the reliability and validity of the questionnaire. Data analysis involved descriptive and inferential statistics, including tabular, graphical, and numerical representations, and multiple linear regression to explore the relationship between digital marketing and organizational agility. Results indicated that social media, mobile, and website marketing positively influence SACCOs’ organizational agility, with an R-squared value of 0.180. This means that 18% of the variance in organizational agility is explained by these digital marketing strategies. However, the moderate explanatory power suggests other factors also impact organizational agility. The study encourages decision-makers to integrate digital strategies into a broader framework of organizational transformation and adaptation. The findings contribute to the understanding of how digital marketing strategies intersect with organizational agility, emphasizing the importance of a holistic approach to digital integration in enhancing SACCOs’ resilience and responsiveness to change. In conclusion, the study highlights the significant role of digital marketing in enhancing the organizational agility of SACCOs, indicating that by adopting comprehensive digital strategies, SACCOs can improve their resilience, responsiveness to change, and overall engagement with their ecosystem.